Alternatives to retaliation - Dores, A. (Conference books: Alternatives to imprisonment, 2018)
Alternatives to imprisonment have turned out to be practical ways of extending and expanding the criminal justice system. Resistance to the use of penalties to correct antisocial behavior has not proved sufficient to transform either these behaviors or the attitudes of states and societies to undesirable practices. Political resistance to abuse of power inside prisons has not been met through prison reforms that include alternatives to imprisonment. An opposition to feelings of retaliation in politics and criminal justice requires the use of a cognitive horizon broader than criminal law. Changing states of mind mobilized in the face of crime requires a study of how criminal institutions are part of the evolution of modern relations between states and societies. Instead of denying that the penalties use the spirit of retaliation as a form of social satisfaction and institutional legitimation, correctly claiming that in previous times the situation of abuse of the victims was more intense, we must understand what is the spirit of retaliation, and how it works. Without which a fruitful discussion on how to guide the opposition to abuse of the use of prison sentences is unproductively circumscribed. One must denounce the hyperdisciplinarity in the social sciences that accepts that prison studies reinforce the idea of isolation of prisons in relation to societies and the state. The conceptualization of the social states of mind, in particular, the spirit of retaliation, serves this purpose.